Performance Enhancement of Evacuated Tube Solar Collectors Using Fe3O4 Nanoparticle‐Enhanced Phase Change Materials for Efficient Thermal Energy Storage - T. Sathish; R. Saravanan; Jayant Giri; Rasan Sarbast Faisal; Tariq Alkhrissat; Nidhal Becheikh; Boutheyna Belhaj Bettaieb; A. Johnson Santhosh (Engineering Reports, 2025)
ABSTRACT One of the most efficient solar thermal systems for water heating and thermal energy storage is the evacuated tube solar collectors (ETSC). Glass tubes are vacuum sealed to minimize heat loss while maximizing solar absorption. This study aims to enhance ETSC performance with the use of iron oxide (Fe3O4) nanoparticles infused phase change materials (PCM). The Fe3O4 concentration was varied at three levels: 0.2 wt.%, 0.4 wt.%, and 0.6 wt.%, and they were tested in terms of fluid temperature, heat absorption, thermal efficiency, and exergy efficiency by experimental analysis. The results show that the inclusion of Fe3O4 nanoparticles greatly increases thermal conductivity and thus improves heat transfer and storage. With growth of 0.6 wt.% Fe3O4, the fluid temperature increased from 58.4°C to 94.5°C, and heat absorption increased from 2516.9 W to 3804.1 W, increasing thermal efficiency from 46.1% to 83.5% and exergy efficiency from 31.2% to 45.2%. To decrease the irreversibility, energy efficiency was improved. The proposed system exhibited enhanced thermal diffusivity, reduced subcooling, and micro‐convective currents due to the addition of Fe3O4 nanoparticles. The potential use of Fe3O4 based Ne‐PCM was experimentally verified, suggested as a sustainable, energy‐efficient thermal storage material for solar thermal applications.